PECTORALIS MAJOR MYOCUTANEOUS FLAP SUCCESS RATE IN SURGICAL MANAGEMENT OF ORAL CANCER - Saeed Ullah Shah,; Hina Jabeen,; Fatima Waseem,; Haleema Dilawar, (Journal of Ayub Medical College Abbottabad, 2024)
Background: The recurrence rate of Oral squamous cell carcinoma is between 26.5% and 56.3% of cases. The majority of handling failures are confined & local-regional. However, there is debate regarding the best course of action for these patients with recurring oral Malignancy. The objective of the study was to assess the efficacy of the flap in the reconstruction of oral cancer patients and the complications that can result from it. Methodology: The study was conducted in Zia-Uddin Hospital, Karachi, Pakistan from 2020 to 2022. Forty patients of recurrent oral cancer, who underwent salvage surgery with a pectoralis major myocutaneous flap were included in the study. Information was taken from the case notes, & the clinical follow-up of the patients were done between one month and one year. Results: The surgery had an 80% overall success rate. Twenty patients (57.1%) experienced difficulties, including 17 (48.6%) who had flap-related issues. Seven patients (20%) experienced problems unrelated to the flap, such as temporomandibular joint pain and haemorrhage of the chest incision. 9 patients (25.7%) experienced major difficulties, compared to 8 patients (22.9%) who experienced minor complications. Conclusion: For the dependable restoration of significant soft tissue abnormalities brought on by the excision of recurrent oral cancer, the pectoralis major myocutaneous flap was found to be a good option. The main issues were related to the reconstruction site. Salvage surgery helps a lot of patients, and some of them can live for two to four years after the procedure.